THE USAGE OF "OCTREOTIDE-DEPOT" FOR THE PREVENTION OF POSTOPERATIVE PANCREATITIS AFTER EXTENDED SURGERY OF MALIGNANT TUMORS OF THE STOMACH, ESOPHAGUS AND THE CARDIA - V. M. Khomyakov; A. V. Ivanov (Исследования и практика в медицине, 2016)
Surgical treatment of patients with gastric cancer with extended lymph node dissection often leads to the primary (intra-operative injury) and secondary (inflammatory processes in the postoperative period) damage to the parenchyma of the pancreas. The incidence of pancreatitis in the postoperative period, according to various authors, reaches 20% or more. Synthetic analogues of somatostatin occupy the special place among the pharmacological methods of prophylaxis. Earlier studies have shown a significantly lower rate of complications, including the formation of pancreatic fistula after operations on the pancreas when using somatostatin analogues. Usage of prolonged SST analogues for the prevention of postoperative pancreatitis remains a matter of research. The article presents a review of existing literature and own experience with prophylactic use of «Оctreotide depot » in patients with malignant tumors of the stomach, esophagus and the cardia